Geological hazards and their control in China - Zhou, Pinggen; Liu, Yuan (Journal of Nepal Geological Society, 2000)
The paper describes the main types of geological hazard and associated risk in China. The engineering geological achievements and problems are also discussed together with the developing trends and strategies for controlling the geological hazards within the next 10 years. The paper summarises the mechanism of failure of mass movements in China as well as the various combinations of engineering geological and geotechnical measures for controlling different types of geological hazard. A good hazard monitoring system (which is made up of three types of monitoring method) and efficient administrative arrangements are stressed.